The burden of hospital-attended influenza in Norwegian children - Bøås, Håkon; Bekkevold, Terese; Havdal, Lise Beier; Kran, Anne-Marte Bakken; Rojahn, Astrid Elisabeth; Størdal, Ketil; Debes, Sara; Døllner, Henrik; Nordbø, Svein Arne; Barstad, Bjørn; Haarr, Elisebet; Vázquez Fernández, Liliana; et al. (Frontiers in Pediatrics, 2022)
Abstract: Background: Norwegian health authorities do not recommend universal pediatric vaccination against seasonal influenza. We aimed to estimate the incidence of influenza by age and underlying medical conditions in hospitalized Norwegian children aged <18 years. Methods: Active surveillance for influenza in children <18 years was implemented in five hospitals during 2015–18. Children with respiratory symptoms and/or fever were prospectively enrolled and tested for influenza. Surveillance data were linked to health registry data to estimate the national burden of influenza in hospitals. Results: In 309 (10%) out of 3,010 hospital contacts, the child tested positive for influenza, corresponding to an average incidence of 0.96 hospital-attended influenza cases per 1,000 children <18 years of age. Children <1 year of age (3.8 per 1,000 children) and children with underlying medical conditions (17 per 1,000 children with bronchopulmonary dysplasia) had the highest average incidence. Among <1 year old children, 3% tested positive for influenza, compared to 25% for children aged 6–17. Few children were vaccinated against influenza. Conclusions: Children <1 year of age and children with underlying medical conditions had a higher incidence of influenza requiring hospital treatment compared to the general population. Effective interventions against seasonal influenza for children in Norway should be considered.